Analisis Strategi Pemasaran Dalam Meningkatkan Daya Saing Industri Batik Tulis Giriloyo - Efni Yulia Santri Harahap; Suhairi Suhairi; Musdiansyah Putra; Nabila Ramadhani (Transformasi Manageria: Journal of Islamic Education Management, 2024)
Marketing strategy is a way to create a sustainable competitive advantage for both companies that produce goods and services. Market competition is a major challenge for entrepreneurs. One of the Indonesian batik production industries is located in the village of Wukirsari. The purpose of this research is to analyze the competitive marketing strategy of the global Giliroyo batik industry. In this study, the authors used a qualitative descriptive method where the data collection technique used was a literature study. According to the survey results, the marketing strategy of the global Jiriroyo tie-dye industry consists of a product strategy, a pricing strategy, a sales promotion strategy and a placement strategy, which are commonly referred to as the 4Ps. Kata Kunci : Strategy, competitiveness, culture, global marketing, Girloyo's deaf batik